2020
DOI: 10.1161/jaha.120.017086
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Arrhythmias in Clinically Manifest Cardiac Sarcoidosis: Incidence, Burden, Predictors, and Outcomes

Abstract: Background Recent data have suggested a substantial incidence of atrial arrhythmias (AAs) in cardiac sarcoidosis (CS). Our study aims were to first assess how often AAs are the presenting feature of previously undiagnosed CS. Second, we used prospective follow‐up data from implanted devices to investigate AA incidence, burden, predictors, and response to immunosuppression. Methods and Results This project is a substudy of the CHASM‐CS (Cardiac Sarcoidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…However, no association was observed between hypertension and HF likely due to the inclusion of other predictors of cardiovascular disease. Risks of diabetes and atrial fibrillation peak immediately after sarcoidosis diagnosis 4 21 22 and although it is disputed whether the latter is a manifestation of cardiac sarcoidosis, 11 12 their presence might lead to diagnosis of HF. A large proportion of future HF cases (>35%) could therefore be attributed to factors unrelated to sarcoid heart involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association was observed between hypertension and HF likely due to the inclusion of other predictors of cardiovascular disease. Risks of diabetes and atrial fibrillation peak immediately after sarcoidosis diagnosis 4 21 22 and although it is disputed whether the latter is a manifestation of cardiac sarcoidosis, 11 12 their presence might lead to diagnosis of HF. A large proportion of future HF cases (>35%) could therefore be attributed to factors unrelated to sarcoid heart involvement.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Cardiac sarcoidosis overtly or covertly affects 5%–30% of patients and commonly manifests with ventricular arrhythmias (12-fold increased risk associated with sarcoidosis, 7 conduction anomalies, sudden cardiac arrest or death, 6 8–10 and rarely as atrial fibrillation). 11 12 Data on the relative contribution of traditional and sarcoidosis-specific risk factors to HF are scarce. 6 Because the underlying mechanisms leading to HF in sarcoidosis may vary greatly, it is critical to examine the factors that contribute the most to HF occurrence, which could aid early identification of at-risk patients who might be targeted with the appropriate preventive, diagnostic or therapeutic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation had a reported prevalence of 32% in 1 single-center study of individuals with CS. 103,104 Atrial fibrillation is more common in individuals with CS who have atrial tracer uptake on FDG-PET scan 105 or myocardial LGE on CMR (although none of these atrial findings are specific to sarcoidosis). Limited data suggest that immunosuppression may reduce the burden of atrial arrhythmias.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…Limited data suggest that immunosuppression may reduce the burden of atrial arrhythmias. 104 Anticoagulation and arrhythmia management are the same for individuals without CS, and atrial fibrillation ablation appears to be of similar efficacy in individuals with and those without CS. 106 Ventricular Arrhythmia Ventricular tachycardia and fibrillation are among the most feared complications of CS and may be the primary presentation.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation